Extension of Some Generalized Hermite-Type Interpolation Operators to the Triangle with One Curved Side. (10th December 2019) - Cătinaş, Teodora
Abstract: We construct some generalized Hermite-type interpolation operators for the case of a triangle with one curved side, and we consider their product and Boolean sum operators. We study the interpolation properties of these operators, the orders of accuracy and the remainders of the interpolation formulas. Finally, we give some numerical examples.